Republic of Madagascar : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that macroeconomic developments in Madagascar in 2003 and 2004 were dominated by the sharp depreciation of the national currency, and rising inflation pressures, with year-over-year consumer price inflation reaching 30 percent at end-February 2005. At the same time, the current account deficit widened considerably in 2004. In the medium term, real GDP growth is expected to average 6 percent per year, and fiscal consolidation is projected to continue, driven by an improvement of revenue performance and modest expenditure increases.